KORELASI KEBIASAAN KONSUMSI PANGAN DENGAN PREVALENSI PENYAKIT GINJAL KRONIS DI INDONESIA - Wijiastutik, Yuni; Ramadhan, Wahyu (Persagi, 2023)
Chronic kidney disease is associated with reduced quality of life, increased healthcare spending, and premature death. This analysis aims to obtain an overview of the relationship between food consumption habits and the prevalence of chronic kidney disease in Indonesia. This study analyzes aggregate data at the provincial level related to chronic kidney failure with selected variables. All provinces were taken as samples. In addition to the prevalence of chronic kidney disease, 4 other variables analyzed as independent variables were the proportion of habitual consumption of fatty/cholesterol/fried foods ≥ 1 time per day, the proportion of habitual consumption of meat/chicken/fish processed with preservatives ≥ 1 time per day, the proportion the habit of consuming soft drinks or carbonated drinks ≥ 1 time per day, the proportion of habitual consumption of energy drinks ≥ 1 time per day. Data were analyzed using scatter plots. The province with the highest prevalence of chronic kidney failure is North Kalimantan Province. The results of the bivariate analysis with scatter plots showed that the habit of consuming fatty/cholesterol/fried foods ≥ 1 time per day, consumption of processed meat/chicken/fish with preservatives ≥ 1 time per day, and consumption of soft drinks or carbonated drinks ≥ 1 time has a positive relation for the prevalence of chronic kidney failure, while the consumption of energy drinks is negatively related to the prevalence of chronic kidney failure in Indonesia. The high prevalence of chronic kidney disease in Indonesia illustrates that public awareness still needs to be increased regarding food consumption habits in the family environment.